2020
DOI: 10.3390/ijerph17020524
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Assessment of Complex Urban Public Spaces

Abstract: Risk events frequently occur in “complex urban public spaces” (CUPSs) and cause serious economic losses and casualties. To reduce the risks and enhance the system resilience, this paper formulates a theoretical framework to assess the resilience of CUPSs. Resilience is defined as the ratio of preparedness to vulnerability, according to the implication of the concept. Three-level practical indicator systems were established for these two dimensions, respectively. Furthermore, a hybrid approach combining the Ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 38 publications
0
15
0
3
Order By: Relevance
“…According to the aforementioned facts, the disaster preparedness refers to the preparation of activities and resources designed to improve the system capacities and protection abilities in advance, which corresponds to the interpretation of the resilience as the ability of a system to resist disruption by reducing the initial negative impacts (absorbability), adapting itself to disruption (adaptability), and recovering from disruption (restorability) [ 100 ]. The relation between preparedness and resilience can be seen by the implication of the resilience as the ratio of this preparedness to vulnerability of the system under consideration [ 100 , 101 , 102 ]. The higher the preparedness level, the higher the resilience and the higher the vulnerability, the lower the resilience [ 102 ].…”
Section: Disaster Preparedness-theoretical Frameworkmentioning
confidence: 99%
“…According to the aforementioned facts, the disaster preparedness refers to the preparation of activities and resources designed to improve the system capacities and protection abilities in advance, which corresponds to the interpretation of the resilience as the ability of a system to resist disruption by reducing the initial negative impacts (absorbability), adapting itself to disruption (adaptability), and recovering from disruption (restorability) [ 100 ]. The relation between preparedness and resilience can be seen by the implication of the resilience as the ratio of this preparedness to vulnerability of the system under consideration [ 100 , 101 , 102 ]. The higher the preparedness level, the higher the resilience and the higher the vulnerability, the lower the resilience [ 102 ].…”
Section: Disaster Preparedness-theoretical Frameworkmentioning
confidence: 99%
“…In a general sense, economic resilience is understood as the response of the system to a specific stimulus or shock or as the ability to avoid and manage natural and anthropogenic risks [20] (p. 16), [21] (p. 2), [22] (p. 524). In the research context, the term is used to describe the relationships occurring in the observed entity during and after the interference.…”
Section: The Notion Of Economic Resilience and Its Determinantsmentioning
confidence: 99%
“…En este sentido, se puede considerar que, en el desarrollo de las metodologías para evaluar la resiliencia de los sistemas urbanos, además de contar con un marco metodológico de indicadores se requiere determinar la sensibilidad del valor de resiliencia para la variación de diferentes indicadores, así como definir las estrategias que mejoran el nivel de resiliencia de los sistemas urbanos. Efectivamente, la simulación de resiliencia es una dirección para futuras investigaciones, en la medida que la variación de la capacidad de recuperación del sistema podría simularse en función de la variación de diferentes indicadores y, por lo tanto, se podrían determinar los indicadores importantes para la resiliencia del sistema, y luego se podrían formular estrategias útiles para mejorar la resiliencia del propio sistema (Xu, Li y Wang, 2020).…”
Section: Construcción De La Resiliencia En La Ciudad De Méxicounclassified
“…Como parte de los marcos de evaluación de la resiliencia, su medición requiere la construcción de indicadores que respondan a un conjunto de criterios, los cuales deben establecerse dependiendo del contexto y las dimensiones temporales y espaciales (Xu, Li y Wang, 2020). La construcción de resiliencia es un proceso a largo plazo (Holden et al, 2016); debido a las incertidumbres inherentes al desarrollo de una ciudad, por sus constantes cambios, así como por las propiedades emergentes que surgen de la interacción entre los componentes de cualquier sistema complejo (Sharifi, 2016).…”
unclassified